A gas phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method
By adopting horizontal gradient solidification methods and gas doping technology during the growth of compound semiconductor crystals, the existing technologies have the problems of the deficit and uneven electrical performance of the existing technology compound semiconductor crystals. Crystallization has improved utilization and reduced costs.
Patent Information
- Application Number
- CN202210279110.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-03-21
AI Technical Summary
The existing compound semiconductor crystal growth methods and doping technologies have problems of intrinsic defects and uneven electrical properties, resulting in low utilization of crystals and high production costs.
The gas -phase doping method based on the horizontal gradient solidification method is adopted to strictly control the temperature and gas pressure of the doping agent through the multi -segment temperature -controlled crystal growth furnace to achieve the uniform distribution of dopia at different growth stages and the sufficient response in the crystal.
The radial and axial uniform doping of the semiconductor crystal of the compound, improve the crystal quality and performance of the crystal, increase the utilization rate, and reduce the production cost.
Smart Images

Figure CN114855261B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor crystal preparation, and in particular relates to a gas phase doping method for growing compound semiconductor single crystals based on a horizontal gradient solidification method. Background Art
[0002] With the development of electronic materials for semiconductor devices and integrated circuits, the research on semiconductor single crystals has now developed to the third generation. The electron mobility of compound semiconductors is much faster than that of the first generation of silicon semiconductors, and is suitable for high-frequency transmission. It is used in radio communications such as mobile phones, base stations, wireless local area networks, satellite communications, satellite positioning, etc.; at the same time, because compound semiconductors have direct band gaps, they can be used in the field of light emission, such as light-emitting diodes (LEDs), laser diodes (LDs), optical receivers (PINs), and solar cells. Therefore, compound semiconductors can be used to manufacture ultra-high-speed integrated circuits, microwave devices, lasers, optoelectronics, and radiation-resistant and high-temperature-resistant devices, which are of great significance to national defense, aerospace, and high-tech research.
[0003] At present, the main methods for growing compound semiconductor single crystals are the vertical Bridgman method, the mobile heater method, the Czochralski method, the vertical gradient solidification method, and the horizontal gradient solidification method. Unlike crystals of single element systems such as silicon and germanium, compound semiconductors usually produce partial pressures at high temperatures and are not suitable for Czochralski growth in an open system. In order to prevent the stoichiometric ratio deviation caused by the partial pressure during the growth of compound semiconductor crystals, a crystal growth method using a crucible as a closed system is selected. Even so, the grown compound semiconductor single crystals will still have intrinsic defects, and the intrinsic electrical properties of semiconductor materials usually cannot meet the requirements of device use. Therefore, in order to adjust and control the intrinsic defects and electrical properties of semiconductors, the following two methods are usually used:
[0004] 1. Doping during the growth process, for example: in the literature "Terterian S, Chu M, Ting D, et al. Uniformity and reproducibility studies of low-pressure-grown Cd 0.9 0Z 0.1 0Tecrystalline materials for radiation detectors[J].Journal of electronicmaterials,2003,32(7):796-802." A 6-inch long Cd2O3 crystal grown by vertical Bridgman method was used. 0.9 Zn 0.1The radial and axial Zn and In contents of Te:In crystals were measured. However, due to the influence of the segregation coefficient, the Zn and In contents were unevenly distributed along the axial and radial directions, resulting in a difference of 1 to 2 orders of magnitude in the resistivity in the radial and axial directions.
[0005] Similarly, in the literature "Zhang J, Wang L, Min J, et al. Characterization of CdMnTecrystal grown with vertical Bridgman method under Te-rich conditions [J]. Physica Status Solidi, 2014, 11 (7-8): 1174-1177.", the In component in CdMnTe:In grown by the vertical Bridgman method was analyzed. The segregation coefficient of the main dopant In in CdMnTe is small, resulting in an order of magnitude difference in the In content in the crystal, leading to resistivity inhomogeneity.
[0006] 2. After the semiconductor single crystal material process is completed, specific elements are often added into the semiconductor material through diffusion, ion implantation, and alloying processes to obtain semiconductor single crystal materials with required electrical properties. Among them, the diffusion concentration of semiconductor materials prepared by diffusion process varies significantly with depth, and the doping uniformity is not good, which requires high process control accuracy. The ion implantation process equipment is expensive and complicated, and the crystal structure is easily damaged due to the collision of incident ions during the implantation process. During alloying doping, the dopant and raw material are mixed, and segregation is easily produced due to uneven mass transfer of the melt, resulting in uneven distribution of the dopant and even precipitation to the tail end of the ingot. When large-sized single crystals are grown, the unevenness caused in the radial and growth directions becomes more obvious due to the increase in the diameter and length of the ingot, which reduces the crystal utilization rate and increases the cost of industrial production.
[0007] Therefore, in view of the many problems caused by the common growth methods and doping technologies of compound semiconductor crystals, it is necessary to propose a new method for growing compound semiconductor crystals. Summary of the invention
[0008] The purpose of the present invention is to solve the many problems caused by the common growth methods and doping technologies of existing compound semiconductor crystals, and propose a gas phase doping method for growing compound semiconductor crystals by horizontal gradient solidification method.
[0009] To achieve the above purpose, the technical solution provided by the present invention is:
[0010] A gas phase doping method for growing a compound semiconductor single crystal based on a horizontal gradient solidification method, which is special in that it comprises the following steps:
[0011] 1) In a dry environment protected by an inert atmosphere, the growth raw materials and dopants required for the compound semiconductor are weighed according to the stoichiometric ratio, and are placed in a clean and dry first container and a second container respectively, and the first container and the second container are placed together in a third container (the placement position of the first container and the second container and the specific distance between the two need to be determined according to the temperature field of the actual furnace body obtained by the test), and the third container is evacuated (the vacuum degree reaches the required pressure) and sealed;
[0012] 2) placing the third container sealed in step 1) in a multi-stage temperature-controlled crystal growth furnace, applying a temperature field to the third container, controlling the temperature field so that the growth raw materials are completely melted into a high-temperature molten liquid in the temperature field, and maintaining the temperature at a temperature higher than the melting point of the compound semiconductor so that the growth raw materials are fully reacted and mixed evenly to form a polycrystalline material;
[0013] 3) After the polycrystalline material in step 2) is synthesized, the temperature of the area where the first container is located is lowered to the melting point of the compound semiconductor, and the temperature of the multi-stage temperature-controlled crystal growth furnace is controlled according to the cooling curve, so that the polycrystalline material is selectively grown under the horizontal temperature gradient, and at the same time, the temperature of the second container is gradually increased until the dopant evaporates, so that the vapor pressure of the dopant in the second container is greater than the vapor pressure in the first container, driving the gas phase dopant to diffuse to the first container area and be incorporated into the crystal in the selective growth stage, that is, the dopant is incorporated into the melt in the gas phase;
[0014] 4) After the crystal selection growth stage in step 3 is completed, the isodiametric growth stage is entered, the temperature of the area where the second container is located is increased, the gas pressure of the dopant is increased, and the doping concentration in the isodiametric growth stage is made consistent with the concentration in the crystal selection growth stage by adjusting the gas pressure; in the late isodiametric growth stage, since the quality of the dopant in the second container is reduced, it is necessary to continue to increase the temperature of the area where the second container is located, so that the doping gas pressure in the late isodiametric growth stage is the same as that in the early isodiametric growth stage, so that the doping concentration in the late isodiametric growth stage is consistent with that in the early isodiametric growth stage (by accurately controlling the temperature of the dopant, the gas pressure in the crystal selection growth stage is consistent with the pressure in the early and late isodiametric growth stages. At a certain temperature, the pressure is positively correlated with the amount of the substance, so the pressure can be controlled by adjusting the temperature, and the doping concentration can be further controlled)
[0015] 5) After the equal diameter growth stage in step 4) is completed, the semiconductor crystal in the first container is subjected to in-situ annealing. In order to prevent the gas phase dopant in the cavity from condensing to the low temperature point of the third container, causing uneven doping, the temperature of the area where the second container is located should be kept higher than the temperature of the area where the first container is located;
[0016] 6) After the annealing in step 5) is completed, the temperature of the multi-stage temperature-controlled crystal growth furnace is lowered to room temperature, the entire growth process is completed, and the growth tube is taken out to obtain a uniformly doped compound semiconductor single crystal.
[0017] Furthermore, in step 1), a high-purity growth raw material with a purity of 99.99999% (7N) and a dopant are loaded so that the total mass of the growth raw material after melting is 1 to 10 times the inner diameter of the first container;
[0018] The dopant content is 100ppb to 1000ppm;
[0019] The third container is evacuated to a vacuum degree of 5×10 -4 Pa~5×10 -7 Pa.
[0020] Furthermore, in step 2), the third container sealed in step 1) is placed in a multi-stage temperature-controlled crystal growth furnace, the temperature of the area where the first container is located is gradually increased from low to high to the melting point temperature of each element of the compound semiconductor and kept at the melting point temperature of each element for 2 to 6 hours, and finally the temperature is increased to 20 to 50°C above the melting point of the compound semiconductor and kept for 6 to 48 hours (the first container of the multi-stage temperature-controlled crystal growth furnace can be set) to allow the growth raw materials in the first container to fully react and mix evenly to form a polycrystalline material.
[0021] Further, in step 3), the temperature of the first container is lowered to the melting point of the compound semiconductor at a rate of 20 to 40°C / h, and the temperature of the multi-stage temperature-controlled crystal growth furnace is controlled to make the polycrystalline material undergo selective crystal growth under a horizontal temperature gradient of 5 to 30°C / cm, and the crystal growth rate is 0.1 to 1 mm / h, so as to prevent the crystal growth gradient and rate from being too large to generate holes and dendrites;
[0022] The temperature of the area where the second container is located is increased at a rate of 30 to 50° C. / h, so that the vapor pressure of the dopant in the second container is greater than the vapor pressure in the first container.
[0023] Furthermore, in step 4), after the crystal selection growth stage is over, the crystal enters the isodiametric growth stage. Under the same length, the volume of the isodiametric growth stage is 3 to 8 times that of the crystal selection growth stage. In order to ensure the uniformity of the dopant during the growth process, it is necessary to accurately adjust the temperature of the isodiametric growth stage to adjust the gas pressure according to the dopant mass required for the isodiametric growth stage, so as to maintain the same doping concentration as that in the crystal selection growth stage; wherein the temperature control accuracy is ±0.5°C.
[0024] Furthermore, in step 5), the first container is subjected to in-situ annealing and maintained at a set temperature for 24 to 96 hours;
[0025] The temperature of the second container is 20-50° C. higher than that of the first container, so as to avoid the dopant from condensing at the low temperature point of the third container and to make the dopant completely vaporized and incorporated into the crystal as much as possible.
[0026] Furthermore, in step 6), the cooling rate is 10-50° C. / h to prevent dendrites and microcracks from being generated inside the crystal due to rapid cooling after the growth is completed, and the power is turned off after the furnace temperature drops to room temperature.
[0027] Furthermore, in step 1), the mass of the growth raw material and dopant added is such that the length of the growth raw material after melting is 3 to 8 times the inner diameter of the first container;
[0028] In step 2), the temperature is raised to above the melting point of the compound semiconductor and then kept at this temperature for 12 to 36 hours;
[0029] In step 3), the temperature gradient in the horizontal direction is 10-20°C / cm;
[0030] In step 5), the first container is subjected to in-situ annealing and maintained at a set temperature for 48 to 72 hours to eliminate the internal stress in the growing crystal;
[0031] In step 6), the cooling rate is 20-40°C / h.
[0032] Furthermore, the first container, the second container and the third container are quartz crucibles, quartz crucibles, graphite crucibles, alumina crucibles, platinum crucibles or crucibles coated with carbon films.
[0033] At the same time, the present invention also provides a compound semiconductor single crystal, which is special in that it is prepared by the above method.
[0034] Principle of the present invention:
[0035] Gas phase doping refers to the technology of evaporating dopants into gaseous form and entering semiconductors at high temperatures. The amount of doped atoms entering the crystal lattice is basically proportional to the partial pressure of the doping gas. Therefore, the control of doping concentration is mainly achieved by adjusting the gas pressure of the dopant, and the gas pressure is mainly achieved by adjusting temperature control.
[0036] The present invention introduces gas phase doping technology in the horizontal gradient solidification method, separates the dopant from other raw materials required for crystal growth, uses a multi-stage temperature-controlled crystal growth furnace, strictly controls the temperature of the dopant to regulate the gas pressure of the dopant at different growth stages, and enables the gaseous doping elements to be doped at the solid-liquid interface and the high-temperature melt at the same time. Compared with the vertical Bridgman method, when the horizontal gradient solidification method grows, the melt of the horizontal gradient solidification method is free space. When the gas phase doping is carried out in the horizontal gradient solidification method, the cavity above the melt is filled with the doping atmosphere by accurately controlling the temperature of the dopant raw material, and the effective reaction contact area between the doping atmosphere and the melt is increased, which is conducive to the full reaction of the dopant and the melt. At the same time, during the horizontal gradient solidification process, the doping atmosphere can be doped from the cavity to the solid-liquid interface, reducing the diffusion path of the dopant. Accurate temperature control of the dopant at different crystal growth stages ensures the uniformity of doping and lattice integrity of the dopant, thereby achieving the regulation of defects and electrical properties, and obtaining radially and axially uniform compound semiconductor crystals.
[0037] The advantages of the present invention are:
[0038] 1. Based on the compound semiconductor crystal growth technology, in order to solve the problems of intrinsic defects and uneven electrical properties in the compound semiconductor growth process, the present invention designs a gas phase doping method for growing compound semiconductor single crystals based on the horizontal gradient solidification method. The method separates the growth raw material and the dopant, controls the temperature through a multi-stage temperature-controlled crystal growth furnace, and realizes the synthesis, crystal growth and annealing process of polycrystalline materials in the same container at the same time. According to the temperature design, the temperature of the dopant is strictly controlled to regulate the gas pressure of the dopant at different growth stages, so that the gaseous doping elements are incorporated into the lattice position inside the crystal during the crystal growth process, which can ensure the doping uniformity and lattice integrity of the dopant during the whole growth process, thereby realizing defect compensation and uniform regulation of electrical properties, obtaining radially and axially uniform semiconductor crystals, improving the crystallization quality and performance of semiconductor crystals, and effectively improving crystal utilization and reducing costs.
[0039] 2. The present invention adopts a multi-stage temperature-controlled crystal growth furnace, and the compound semiconductor growth raw materials and dopants are respectively loaded into clean and dry containers; the compound semiconductor growth raw materials are fully mixed to generate polycrystalline materials, and the temperatures of the polycrystalline materials and dopants are respectively adjusted, and gas phase doping is started from the crystal selection process. After the crystal selection is completed, the equal-diameter growth process begins, and the temperature and pressure of the dopant are accurately controlled so that the dopant concentration in the equal-diameter growth section is the same as the dopant concentration in the crystal selection section. In the later stage of equal-diameter growth, the temperature of the dopant section is increased so that the remaining trace dopant can be completely vaporized, ensuring that the doping concentration in the later stage of equal-diameter growth is consistent with that in the early stage of equal-diameter growth, that is, by accurately controlling the temperature, the steam pressure in different growth stages is controlled to adjust the doping concentration during the crystal growth process. After the growth is completed, the grown crystal is annealed in situ. During the annealing process, the temperature at the end of the dopant container is controlled to be higher than the growth end to prevent the gas phase dopant in the cavity from condensing toward the cold end. After the annealing is completed, the furnace body is cooled to room temperature at a certain rate. After the growth process is completed, the growth container is taken out to obtain a uniformly doped semiconductor crystal. The present invention combines the horizontal gradient solidification method with the gas phase doping technology, applies the gas phase doping to the whole process of crystal growth, and realizes the synthesis, growth and annealing of polycrystalline materials in one container by accurately controlling the temperature of the furnace body. During the crystal growth process, the temperature field is designed according to the relationship between the dopant concentration and the temperature and pressure, and the dopant temperature is accurately controlled to adjust the dopant gas pressure, so that the gas phase dopant can fully react with the melt during the crystal growth process, and the dopant is fully diffused in the solid-liquid interface and the melt, and uniformly doped into the crystal internal lattice position, thereby improving the doping uniformity and lattice integrity, thereby realizing the uniform regulation of defect compensation and electrical properties, and obtaining a semiconductor crystal uniformly doped in the radial and axial directions. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A process flow chart for the implementation of the present invention;
[0041] Figure 2 A schematic diagram of a crystal growth device and a vapor phase doping process according to an embodiment of the present invention;
[0042] (a) is a diagram of a crystal growth device, with the following reference numerals: 1-zirconia insulation board, 2-heating wire, 3-insulation baffle, 4-quartz furnace, 5-nano aerogel insulation blanket, 6-growth raw material, 7-first container, 8-third container, 9-quartz support, 10-dopant raw material, 11-second container, 12-quartz plug;
[0043] (b) Schematic diagram of the vapor phase doping path for growing compound semiconductor crystals using the horizontal gradient solidification method;
[0044] Figure 3 Example 1Cd 0.9 Zn 0.1The X-ray rocking curve of the crystal obtained by doping Se with Te in gas phase;
[0045] Figure 4 Example 2Cd 0.9 Mn 0.1 The X-ray rocking curve and X-ray powder diffraction pattern of the crystal obtained by Te vapor doping Mg;
[0046] Figure 5 Example 3In 0.52 Se 0.48 X-ray powder diffraction pattern of the crystal obtained by vapor phase doping with S. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention:
[0048] Embodiment 1:
[0049] like Figure 1 A gas phase doping method for growing a compound semiconductor single crystal based on a horizontal gradient solidification method comprises the following steps:
[0050] Step 1: According to the CdZnTe phase diagram, weigh high-purity (7N) elemental Cd, Zn, Te growth materials, and dopant Se according to Cd 0.9 Zn 0.1 The stoichiometric ratio of Te is weighed, and the charging mass satisfies that the length of the raw material after melting is 8 times the diameter of the crucible. The Cd, Zn, and Te raw materials are placed in the first quartz crucible, and the dopant Se is placed in the second quartz crucible. The two quartz crucibles containing the raw materials are placed in the third quartz crucible at the same time, and the third quartz crucible is evacuated to a vacuum degree of 5*10 -4 When Pa, the quartz crucible is sealed with an oxyhydrogen flame;
[0051] Step 2: If Figure 2 As shown, the closed third quartz crucible is placed in a multi-stage temperature-controlled crystal growth furnace. According to the temperature setting, the temperature of the first quartz crucible area containing the growth raw materials is raised to 321°C and kept for 2 hours, then raised to 450°C and kept for 6 hours, and then raised to 1130°C and kept for 24 hours, so that the growth raw materials are fully reacted and mixed to form polycrystalline materials;
[0052] Step 3: After the polycrystalline material is homogenized, the furnace is cooled at a rate of 20°C / h to reduce the temperature of the first quartz crucible to Cd 0.9 Zn 0.1The melting point of Te is 1100℃. The horizontal temperature gradient of the first quartz crucible is 20℃ / cm. The growth rate is 0.1mm / h for selective crystal growth. At the same time, the temperature of the second quartz crucible containing the dopant Se is increased to 685℃, so that the dopant Se begins to sublimate into gas phase molecules. With the start of crystal selection, the dopant is vapor-doped into the growing crystal.
[0053] Step 4: Cd 0.9 Zn 0.1 After Te crystal selection is completed, the isodiameter growth stage is entered. The temperature at the second quartz crucible is increased to 690°C, and the gas pressure of the dopant Se is increased to make the doping concentration in the isodiameter growth stage consistent with that in the crystal selection growth stage.
[0054] Step 5: Cd 0.9 Zn 0.1 In the late stage of Te isodiametric growth, the mass of the dopant in the second quartz crucible decreases, and the temperature of the second quartz crucible is slowly increased to 695°C to ensure the same vapor pressure as in the early stage of isodiametric growth, driving the gas phase dopant to diffuse to the first quartz crucible, so that the doping concentration in the late stage of isodiametric growth is consistent with that in the early stage of isodiametric growth.
[0055] Step 6: After the crystal growth is completed, the Cd 0.9 Zn 0.1 The Te:Se crystal was annealed in situ for 72 hours at 900°C, and the temperature of the second quartz crucible was raised to 920°C to prevent the gas phase dopant from condensing at the cold end. After the annealing, the temperature was lowered to room temperature at a rate of 20°C / h. The growth process was completed, and the quartz crucible was removed to obtain a uniformly doped Cd 0.9 Zn 0.1 Te:Se single crystal.
[0056] This embodiment produces a Cd with a diameter of 1 inch and a length of 8 inches. 0.9 Zn 0.1 Te:Se ingot, using X-ray rocking curve measurement to obtain the X-ray rocking curve of the crystal Figure 3 As shown in Figure 1, the half-peak widths of the diffraction peaks at the head and tail are 42.5 arcsec (arc seconds) and 60.12 arcsec, respectively. The concentration of dopant Se was tested by inductively coupled plasma mass spectrometry (ICP-MS) as shown in Table 1. The concentrations of Se in the head, middle, and tail are 4.18 ppm, 4.21 ppm, and 4.16 ppm, respectively.
[0057] Comparative Example 1:
[0058] Step 1: According to the CdZnTe phase diagram, weigh high-purity (7N) elemental Cd, Zn, Te growth materials, and dopant Se according to Cd 0.9 Zn 0.1 The stoichiometric ratio of Te is weighed, and the charging mass satisfies that the length of the raw material after melting is 8 times the diameter of the crucible. The Cd, Zn, Te, and Se raw materials are placed in a quartz crucible at the same time, and the quartz crucible is evacuated to a vacuum degree of 5*10 -4 When Pa, the quartz crucible is sealed with oxyhydrogen flame.
[0059] Step 2: Place the closed quartz crucible in the crystal growth furnace body, and according to the temperature setting, raise the temperature of the quartz crucible area containing the raw materials to 1130°C and keep it warm for 24 hours to allow the growth raw materials and dopants to fully react and mix to form polycrystalline materials;
[0060] Step 3: After the polycrystalline material is homogenized, the furnace is cooled at a rate of 20°C / h to reduce the temperature of the quartz crucible to Cd 0.9 Zn 0.1 The melting point of Te is 1100°C, and the growth is carried out under the conditions of a horizontal temperature gradient of 20°C / cm in the quartz crucible and a growth rate of 0.1 mm / h.
[0061] Step 4: After the crystal growth is completed, cool it down to room temperature at a rate of 20℃ / h, take out the quartz crucible, and you can get Cd 0.9 Zn 0.1 Te:Se single crystal.
[0062] This comparative example produces a Cd having a diameter of 1 inch and a length of 8 inches. 0.9 Zn 0.1 The Te:Se ingot was tested for Se concentration using inductively coupled plasma mass spectrometry (ICP-MS) as shown in Table 1. The Se concentrations in the head, middle, and tail were 3.90 ppm, 4.98 ppm, and 5.73 ppm, respectively.
[0063] Example 2
[0064] Step 1: According to the CdMnTe phase diagram, weigh high-purity (7N) elemental Cd, Mn, Te raw materials, and dopant Mg according to Cd 0.9 Mn 0.1 The stoichiometric ratio of Te is weighed, and the loading mass satisfies that the length of the raw material after melting is 3 times the diameter of the crucible. The Cd, Mn, and Te raw materials are placed in the first quartz crucible, and the dopant Mg is placed in the second quartz crucible. The two quartz crucibles containing the growth raw materials and dopants are placed in the third quartz crucible at the same time. The third quartz crucible is evacuated to a vacuum degree of 5*10- 5 When Pa, the quartz crucible is sealed with oxyhydrogen flame.
[0065] Step 2: Place the closed third quartz crucible in a multi-stage temperature-controlled crystal growth furnace. According to the temperature setting, raise the temperature of the first quartz crucible area containing the growth raw materials to 321°C and keep it for 2 hours, raise the temperature to 450°C and keep it for 6 hours, and raise the temperature to 1120°C and keep it for 36 hours, so that the growth raw materials can fully react and mix to form polycrystalline materials.
[0066] Step 3: After the polycrystalline material is homogenized, the furnace body is cooled at a certain cooling rate to reduce the tip temperature of the first quartz crucible to Cd 0.9 Mn 0.1 The melting point of Te is 1090℃. The first quartz crucible is used for crystal growth under the conditions of a horizontal temperature gradient of 15℃ / cm and a growth rate of 0.5mm / h. At the same time, the temperature of the second quartz crucible containing the dopant Mg is increased to 1107℃, so that the dopant Mg begins to sublimate into gas phase molecules. With the start of crystal selection, the dopant is vapor-doped into the growing crystal.
[0067] Step 4: Cd 0.9 Mn 0.1 After the Te crystal selection is completed, the isodiameter growth stage is entered, and the temperature at the second quartz crucible is raised to 1110°C to increase the vapor pressure of the dopant so that the doping concentration in the isodiameter growth stage is consistent with that in the crystal selection growth stage;
[0068] Step 5: Cd 0.9 Mn 0.1 In the late stage of Te isodiametric growth, the mass of the dopant in the second quartz crucible decreases, and the temperature of the second quartz crucible is slowly increased to 1115°C to ensure the same vapor pressure as in the early stage of isodiametric growth, driving the gas phase dopant to diffuse to the first quartz crucible, so that the doping concentration in the late stage of isodiametric growth is consistent with that in the early stage of isodiametric growth.
[0069] Step 6: After the crystal growth is completed, the temperature is cooled to the annealing temperature of 960°C at a cooling rate of 15°C / h. 0.9 Mn 0.1 The Te:Mg crystal was annealed in situ and kept warm for 48 hours. At the same time, the temperature of the second quartz crucible was adjusted to 1010°C to prevent the residual gas phase dopant from condensing to the cold end. After the annealing, the temperature was slowly cooled to room temperature at a rate of 30°C / h. After the growth process was completed, the quartz crucible was removed to obtain a uniformly doped Cd 0.9 Mn 0.1 Te:Mg single crystal.
[0070] This embodiment produces a Cd with a diameter of 1 inch and a length of 3 inches. 0.9 Mn 0.1 Te:Mg ingot, using X-ray rocking curve to measure the diffraction pattern Figure 4 The half-peak widths of the diffraction peaks at the head, middle and tail of the crystal are 22.06 arcsec, 23.38 arcsec and 33.79 arcsec respectively. The concentration of the dopant Mg tested by ICP-MS is shown in Table 1, where the doping concentrations of Mg at the head, middle and tail are 4.56 ppm, 4.53 ppm and 4.48 ppm respectively.
[0071] Example 3
[0072] Step 1: According to the InSe phase diagram, weigh high-purity (7N) single-element In, Se growth raw materials, and dopant S according to InSe. 0.52 Se 0.48 The stoichiometric ratio is weighed, and the charging mass satisfies that the length of the raw material after melting is 5 times the diameter of the crucible. The In and Se growth raw materials are placed in the first quartz crucible, and the dopant S is placed in the second quartz crucible. The two quartz crucibles containing the growth raw materials and the dopant are placed in the third quartz crucible at the same time. The third quartz crucible is evacuated to a vacuum degree of 5*10 -7 At Pa, the third quartz crucible is closed with an oxyhydrogen flame.
[0073] Step 2: Place the closed third quartz crucible in a multi-stage temperature-controlled crystal growth furnace. According to the temperature setting, slowly increase the temperature of the first quartz crucible area containing the growth raw materials to 157°C and keep it for 2 hours, slowly increase the temperature to 217°C and keep it for 6 hours, and increase the temperature to 935°C and keep it for 12 hours, so that the growth raw materials can fully react and mix to form polycrystalline materials.
[0074] Step 3: After the polycrystalline material is homogenized, the furnace body is cooled at a certain cooling rate to reduce the temperature of the first quartz crucible to In 0.52 Se 0.48 The melting point of S is 885℃, and the first quartz crucible is used for crystal growth under the conditions of a horizontal temperature gradient of 10℃ / cm and a growth rate of 1mm / h. At the same time, the temperature of the second quartz crucible containing dopant S is increased to 445℃, so that the dopant S begins to sublimate into gas phase molecules. With the start of crystal selection, the dopant is vapor-doped into the growing crystal.
[0075] Step 4: In 0.52 Se 0.48 After the crystal selection is completed, the isodiameter growth stage begins. The temperature at the second quartz crucible is slowly increased to 450°C to increase the vapor pressure of the dopant so that the doping concentration in the isodiameter growth stage is consistent with that in the crystal selection growth stage.
[0076] Step 5: In 0.52 Se 0.48 In the later stage of the equal-diameter growth stage, the mass of the dopant in the second quartz crucible decreases, and the temperature of the second quartz crucible is slowly increased to 455°C, so that it can maintain the same vapor pressure as in the early stage of the equal-diameter growth stage, driving the gas-phase dopant to diffuse to the first quartz crucible, so that the doping concentration in the later stage of the equal-diameter growth stage is consistent with that in the early stage of the equal-diameter growth stage.
[0077] Step 6: After the crystal growth is completed, the temperature is lowered to annealing temperature 500°C at a cooling rate of 30°C / h. 0.52 Se 0.48 :S crystal is annealed in situ, the annealing time is 60h, the annealing temperature is 500℃, and the temperature of the second quartz crucible is adjusted to 530℃ to prevent the residual gas phase dopant from condensing to the cold end. After the annealing is completed, the temperature is slowly lowered to room temperature at a rate of 40℃ / h. The growth process is completed, and the quartz crucible is taken out to obtain uniformly doped In 0.52 Se 0.48 :S crystal.
[0078] This embodiment produces an In with a diameter of 1 inch and a length of 5 inches. 0.52 Se 0.48 :S crystal ingot, using X-ray powder diffraction to obtain the crystal diffraction peaks such as Figure 5 As shown, the half-peak width of the diffraction peak is 0.167°. The concentration of the gas phase dopant S tested by ICP-MS is shown in Table 1, where the S doping concentrations of the head, middle, and tail are 266.85ppm, 266.37ppm, and 267.84ppm, respectively.
[0079] Comparative Example 2
[0080] Step 1: According to the InSe phase diagram, weigh high-purity (7N) single-element In, Se growth raw materials, and dopant S according to InSe. 0.52 Se 0.48 The stoichiometric ratio is weighed, and the charging mass satisfies that the length of the raw material after melting is 5 times the diameter of the crucible. The In and Se growth raw materials are placed in the first quartz crucible, and the dopant S is placed in the second quartz crucible. The two quartz crucibles containing the growth raw materials and the dopant are placed in the third quartz crucible at the same time. The third quartz crucible is evacuated to a vacuum degree of 5*10 -7 When Pa, the quartz crucible is sealed with oxyhydrogen flame.
[0081] Step 2: Place the closed quartz crucible in a multi-stage temperature-controlled crystal growth furnace. According to the temperature setting, raise the temperature of the first quartz crucible area containing the growth raw materials to 935°C and keep it warm for 12 hours to allow the growth raw materials to fully react and mix to form polycrystalline materials.
[0082] Step 3: After the polycrystalline material is homogenized, the furnace body is cooled at a certain cooling rate to reduce the temperature of the first quartz crucible to In 0.52 Se 0.48 The melting point of S is 885°C, and the first quartz crucible is grown under the conditions of a horizontal temperature gradient of 10°C / cm and a growth rate of 1mm / h. At the same time, the temperature of the second quartz crucible containing the dopant S is increased to 445°C, so that the dopant S is vapor-doped into the growing crystal during the crystal growth process.
[0083] Step 4: After the growth is completed, cool down to room temperature at a rate of 40°C / h. The growth process is completed, and the quartz crucible is taken out to obtain In 0.52 Se 0.48 :S crystal.
[0084] This comparative example produces an In with a diameter of 1 inch and a length of 5 inches. 0.52 Se 0.48 :S crystal ingot, the concentration of gas phase dopant S tested by ICP-MS is shown in Table 1, wherein the S doping concentrations in the head, middle and tail are 285.39ppm, 267.10ppm and 257.64ppm respectively.
[0085] Table 1 is a statistical table of dopant concentrations from the head to the tail of the crystals obtained in the examples and comparative examples
[0086]
[0087] It can be seen from the above that strictly controlling the temperature of the dopant to regulate the gas pressure of the dopant at different growth stages is extremely important for doping uniformity. At the same time, it also proves that the method of the present invention is more uniform in doping than the existing method.
[0088] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A gas phase doping method for growing compound semiconductor single crystals based on a horizontal gradient solidification method, characterized in that: The following steps are involved: 1) In a dry environment protected by an inert atmosphere, the growth raw materials and dopants required for the compound semiconductor are weighed according to a stoichiometric ratio, and are placed in a clean and dry first container and a second container, respectively, and the first container and the second container are placed together in a third container, and the third container is evacuated and sealed; 2) placing the sealed third container in step 1) in a multi-stage temperature-controlled crystal growth furnace, applying a temperature field to the third container, gradually raising the temperature of the area where the first container is located from low to high to the melting point temperature of each element of the compound semiconductor and keeping it at the melting point temperature of each element for 2 to 6 hours, and finally raising the temperature to 20 to 50° C. above the melting point of the compound semiconductor, keeping it at this temperature for 6 to 48 hours, so that each growth raw material in the first container is fully reacted and evenly mixed to form a polycrystalline material; 3) After the polycrystalline material in step 2) is synthesized, the temperature of the area where the first container is located is reduced to the melting point of the compound semiconductor at a rate of 20 to 40°C / h, and the temperature of the multi-stage temperature-controlled crystal growth furnace is controlled to make the polycrystalline material undergo selective crystal growth under a horizontal temperature gradient of 5 to 30°C / cm, and the crystal growth rate is 0.1 to 1 mm / h; at the same time, the temperature of the area where the second container is located is increased at a rate of 30 to 50°C / h, so that the vapor pressure of the dopant in the second container is greater than the vapor pressure in the first container, driving the gas phase dopant to diffuse into the area of the first container and be incorporated into the crystal in the selective crystal growth stage; 4) After the crystal selection growth stage in step 3) is completed, the equal-diameter growth stage is entered, the temperature of the area where the second container is located is increased, the gas pressure of the dopant is increased, and the doping concentration in the equal-diameter growth stage is made consistent with the doping concentration in the crystal selection growth stage by adjusting the gas pressure; when entering the late equal-diameter growth stage, the temperature of the area where the second container is located is continued to be increased, so that the doping gas pressure in the late equal-diameter growth stage is the same as that in the early equal-diameter growth stage, so that the doping concentration in the late equal-diameter growth stage is consistent with that in the early equal-diameter growth stage; 5) After the equal diameter growth stage in step 4) is completed, the semiconductor crystal in the first container is subjected to in-situ annealing, and maintained at a set temperature for 48 to 96 hours; and the temperature of the area where the second container is located is maintained at 20 to 50° C. higher than the temperature of the area where the first container is located; 6) After the annealing in step 5) is completed, the temperature of the multi-stage temperature-controlled crystal growth furnace is lowered to room temperature to obtain a uniformly doped compound semiconductor single crystal.
2. The vapor phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method according to claim 1, characterized in that: In step 1), the total mass of the growth raw material and dopant added is such that the length of the growth raw material after melting is 1 to 10 times the inner diameter of the first container; The dopant content is 100ppb to 1000ppm; The third container is evacuated to a vacuum degree of 5×10 -4 Pa~5×10 -7 Pa.
3. The vapor phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method according to claim 2, characterized in that: In step 4), after the selective crystal growth stage is completed, the crystal enters the isodiametric growth stage. Under the same length, the volume of the isodiametric growth stage is 3 to 8 times that of the selective crystal growth stage. The temperature of the isodiametric growth stage is precisely adjusted according to the dopant mass required for the isodiametric growth stage to adjust the gas pressure so that it maintains the same doping concentration as that in the selective crystal growth stage. The temperature control accuracy is ±0.5°C.
4. The vapor phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method according to claim 3, characterized in that: In step 6), the cooling rate is 10 to 50° C. / h.
5. The vapor phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method according to claim 4, characterized in that: In step 1), the total mass of the growth raw material and dopant added is such that the length of the growth raw material after melting is 3 to 8 times the inner diameter of the first container; In step 2), the temperature is raised to above the melting point of the compound semiconductor and then kept at this temperature for 12 to 36 hours; In step 3), the temperature gradient in the horizontal direction is 10-20°C / cm; In step 5), the first container is subjected to in-situ annealing and maintained at a constant temperature for 48 to 72 hours at a set temperature; In step 6), the cooling rate is 20-40°C / h.
6. The vapor phase doping method for growing compound semiconductor single crystals based on horizontal gradient solidification method according to claim 1, characterized in that: The first container, the second container and the third container are quartz crucibles, quartz crucibles, graphite crucibles, alumina crucibles, platinum crucibles or crucibles coated with carbon films.
Citation Information
Patent Citations
Preparation method and device for doping semi-insulating gallium arsenide polycrystal with carbon
CN107268085A
Shouldering method in horizontal method gallium arsenide single-crystal drawing process
CN107955971A
Reaction device and semiconductor preparation method for horizontal boat production method
CN108560055A
Gallium arsenide-doped single crystal growth process
CN111893571A